Young adults, alcohol and Facebook: a synergistic relationship. Issue 2 (10th April 2017) - Jones, Sandra C.; Pettigrew, Simone; Biagioni, Nicole; Daube, Mike; Chikritzhs, Tanya; Stafford, Julia; Tran, Julien
Abstract : Purpose: There is a growing body of research into the utilisation of social networking sites (SNS) by alcohol marketers, but less research into how young people utilise SNS to create their own meanings of, and interactions with, alcohol. The purpose of this study was to explore young adults' perceptions of the nexus between alcohol and SNS. Design/methodology/approach: In total, 60 adults aged 18-21 years took part in an intensive data collection process over six months. All references to social media in the interviews, focus groups and written introspections were compiled and analysed. Findings: Results showed social media use stimulates alcohol consumption and alcohol consumption stimulates social media use. Four main themes emerged: social engagement, identity, drinking culture and distancing. Participants reported being constantly exposed to, and often influenced by, images of their peers enjoying themselves while consuming alcohol, with little representation of negative outcomes. Research limitations/implications: The relationship between SNS, social norms and drinking behaviours is complex; there is a need for further research into the dynamics of this relationship to inform social marketing interventions. Originality/value: While there is a body of research into commercial references to alcohol on SNS, there is less research into the ways young people utilise SNS to create their own meanings of, and interactions with, alcohol. The consumer research that has been conducted to date has focused on quantifying references to alcohol and drinking behaviours, observing profiles or surveying users. This study addresses a key gap in the literature that is needed to inform social marketing interventions to reduce excessive alcohol consumption: when, why and how do young people post about alcohol.